Quantifying research output on poverty and non-communicable disease behavioural risk factors in low-income and lower middle-income countries: a bibliometric analysis. Issue 11 (12th November 2017) - Allen, Luke Nelson; Fox, Nicholas; Ambrose, Alissa
Abstract : Objectives: Low-income and lower middle-income countries (LLMICs) bear a disproportionate burden of non-communicable diseases (NCDs). WHO has repeatedly called for more research on poverty and NCDs in these settings, but the current situation remains unquantified. We aimed to assess research output on poverty and NCD risk factors from these countries in relation to upper middle-income and high-income countries. Design: Bibliometric analysis of primary research published between 1 January 1990 and 4 May 2017. We searched 13 databases, combining terms for poverty and NCD behavioural risk factors (tobacco, alcohol, diet and physical activity). Independent dual review was used to screen titles, abstracts and full papers. Two-tailed t-testing and multiple linear regression analyses were used to compare differences in means. Outcomes: (1) Proportion of lead authors affiliated with institutions based in high and upper middle-income countries vs LLMICs. (2) Mean number of citations for publications from each region. (3) Mean journal impact factor for studies from each region. Results: Ninety-one (67%) of the 136 included studies were led by scientists affiliated with LLMIC-based institutions. These authors represented 17/83 LLMICs (20%), and their studies garnered 4.8 fewer citations per paper than studies led by high-income and upper middle-income-affiliated authors; however, this finding was non-significant (P=0.67). Papers led by authors based in high-income and upper middle-income countries were published in journals with a mean impact factor 3.1 points higher than those from LLMICs (4.9 vs 1.7) adjusting for year of publication and number of citations (P<0.001). Conclusions: Most poverty and NCD risk factor research is led by authors from a small number of LLMICs. These studies are being published in relatively low-impact journals, and the vast majority of LLMICs are not producing any research in this area that is vital to their social and economic development. The paucity of domestic evidence must be addressed to inform global policy.